Quaternionic Bézier curves, surfaces and volume - Zube, Severinas (Lietuvos matematikos rinkinys, 2013)
We extended the rational Bézier construction for linear, bi-linear and threelinear map, by allowing quaternion weights. These objects are Möbius invariant and have halved degree with respect to the real parametrization. In general, these parametrizations are in four dimensional space. We analyse when a special the three-linear parametrized volume is in usual three dimensional subspace and gives three orthogonal family of Dupine cyclides.
Keywords: circle; Dupine cyclide; inversion; quaternion